2013
DOI: 10.3934/dcdsb.2013.18.693
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal generalized models of predator-prey systems

Abstract: The method of generalized modeling has been applied successfully in many different contexts, particularly in ecology and systems biology. It can be used to analyze the stability and bifurcations of steady-state solutions. Although many dynamical systems in mathematical biology exhibit steady-state behaviour one also wants to understand nonlocal dynamics beyond equilibrium points. In this paper we analyze predatorprey dynamical systems and extend the method of generalized models to periodic solutions. First, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…Bazykin's model is equivalent to Rosenzweig and MacArthur's model (1963) with density-dependent mortality for the predator. The predator has no density-dependent mortality in previous studies on structural sensitivity and generalized predator-prey models (Kuehn and Gross, 2011;Yeakel et al, 2011). However, density-dependent mortality represents the effects of diseases and/ or competition and can be relevant for a wide range of predator species (Loreau, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bazykin's model is equivalent to Rosenzweig and MacArthur's model (1963) with density-dependent mortality for the predator. The predator has no density-dependent mortality in previous studies on structural sensitivity and generalized predator-prey models (Kuehn and Gross, 2011;Yeakel et al, 2011). However, density-dependent mortality represents the effects of diseases and/ or competition and can be relevant for a wide range of predator species (Loreau, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although circadian rhythms are often suppressed in critically ill patients (Lowry, 2009; Mundigler et al, 2002), there is still a need to very accurately distinguish between movement that is part of a healthy circadian rhythm and a pathological transition between steady states. Generalized models of periodic systems have been studied (Kuehn and Gross, 2011), but not yet applied in the prediction of critical transitions. Random noise is another confounding factor which makes the estimation of partial derivatives from limited data more difficult, although appropriate smoothing of the data may be sufficient to retain predictive power (Lade and Gross, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The examples have also demonstrated that known results about bifurcations and unfoldings carry over easily to generalized models. The same calculations can be carried out for all other local bifurcations which will yield conditions analogous to (42).…”
Section: Bifurcations Of Generalized Modelsmentioning
confidence: 99%
“…However, this approach cannot capture global bifurcations such as saddle-nodes of periodic orbits. Recent work of Kuehn and Gross [42] shows how to extend generalized modeling to periodic orbits for the predator-prey system (1). The main problem is that the generalized parameter β i,k and f i,k,x j become time-dependent functions β i,k (t) and f i,k,x j (t).…”
Section: Nonlocal Generalized Modelsmentioning
confidence: 99%
See 1 more Smart Citation